Floquet-Bloch valleytronics - Sotirios Fragkos; Baptiste Fabre; Olena Tkach; Stéphane Petit; Dominique Descamps; Gerd Schönhense; Yann Mairesse; Michael Schüler; Samuel Beaulieu (Nature Communications)
Abstract Upon time-periodic driving of electrons using electromagnetic fields, the emergence of Floquet-Bloch states enables the creation and control of exotic quantum phases. In transition metal dichalcogenides, broken inversion symmetry within each monolayer results in Berry curvature at the K and K′ valley extrema, giving rise to chiroptical selection rules that are fundamental to valleytronics. Here, we bridge the gap between these two concepts and introduce Floquet-Bloch valleytronics. Using time- and polarization-resolved extreme ultraviolet momentum microscopy combined with state-of-the-art ab initio theory, we demonstrate the formation of valley-polarized Floquet-Bloch states in 2H-WSe2 upon below-bandgap driving with circularly polarized light pulses. We investigate quantum-path interference between Floquet-Bloch and Volkov states, revealing its dependence on the valley pseudospin and light polarization. Extreme ultraviolet photoemission circular dichroism in these non-equilibrium settings reveals the potential for controlling the orbital character of Floquet-engineered states. These findings link Floquet engineering and quantum-geometric light-matter coupling in two-dimensional materials.